Inhibition of EZH2 expression is associated with the proliferation, apoptosis, and migration of SW620 colorectal cancer cells in vitro. (April 2015) - He, Song-Bing; Zhou, Hao; Zhou, Jian; Zhou, Guo-Qiang; Han, Tuo; Wan, Dai-Wei; Gu, Wen; Gao, Lin; Zhang, Yi; Xue, Xiao-Feng; Zhang, Li-Feng; Fei, Min; et al.
Epigenetic changes have been recently recognized as important in human cancers. Enhancer of zeste homologue 2 gene (EZH2) has been shown the overexpression in various human cancers, consistent with a straightforward role of EZH2 as an oncogene, but its function in carcinogenesis is partly contradictory. The role of EZH2 in development of human colorectal cancer (CRC) has not yet been clarified. In the present study, we observed up-regulation of EZH2 expression in tumor tissues from CRC patients. The expression of EZH2 in CRC cell lines is consistent with the trend in cancer tissues using reverse transcription polymerase chain reaction (RT-PCR). We showed that TNM stage and lymph node metastasis in CRC patients are significantly correlated with EZH2 expression levels. EZH2 level of transcription and protein is inhibited by small interfering RNA (siRNA). More importantly, EZH2-siRNA inhibits the proliferation and migration of SW620 cells while promoting their apoptosis, and inducing G0/G1 cell cycle arrest of SW620 cells. Collectively, our results suggest that upregulated EZH2 expression may contribute to the progression of the patients with CRC. A comprehensive study of epigenetic mechanisms and the relevance of EZH2 in CRC is important for fully understanding this disease and as a basis for developing new treatment options in patients with CRC.